STUDY ON THE PRACTICE OF PHYSICAL EXERCISES AT THE AGE OF 14, DURING LEISURE - SALUP Mărioara (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
This study has as main purpose to highlight the importance of practicing physical exercises at any age and also to reveal to what extent secondary level students practice physical exercises independently. One of the important problems of modern society is overweight among children, youth and adults, mainly due to unhealthy diet and lack of exercise. In this study we found a few